2015
DOI: 10.5688/ajpe797100
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Responsibilities of Pharmacy Student Government Associations in Pharmacy Programs

Abstract: Objective. To identify student government designs used by pharmacy programs and to examine their functions, duties, and relationships with other student organizations. Methods. A 21-question survey was developed and distributed to pharmacy deans, who were asked to forward the survey to the leader of their student government organization. Results were analyzed in aggregate.Results. Seventy-one programs responded (56%). Of respondents, 96% had a pharmacy student government association (PSGA). Programs officers g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…14 We found that little data specific to shared governance in schools and colleges of pharmacy existed, aside from a study exploring student governance. 7 However, findings from the annual AACP Faculty Survey, in which assessment of faculty satisfaction with administration and governance is a primary objective, suggest that most pharmacy faculty members are satisfied with the functioning of existing administration and governance structures. 15 For example, in the 2017 survey, 87.3% of the faculty members who responded either agreed or strongly agreed that their school or college provided opportunities for faculty participation in governance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 We found that little data specific to shared governance in schools and colleges of pharmacy existed, aside from a study exploring student governance. 7 However, findings from the annual AACP Faculty Survey, in which assessment of faculty satisfaction with administration and governance is a primary objective, suggest that most pharmacy faculty members are satisfied with the functioning of existing administration and governance structures. 15 For example, in the 2017 survey, 87.3% of the faculty members who responded either agreed or strongly agreed that their school or college provided opportunities for faculty participation in governance.…”
Section: Resultsmentioning
confidence: 99%
“…The only primary literature related to shared governance in schools and colleges of pharmacy is focused on student governance. 7 Thus, little is known about best and successful practices regarding shared governance models within pharmacy education.…”
Section: Introductionmentioning
confidence: 99%
“…Similar feelings were expressed by the participants in this study about their student constituents. These participants did not experience what Kennedy, Ginsburg, Harnois, & Spooner (2015), Klemenčič (2014), Menon (2003), and Miles (2011) have all said, which is that student constituent attitudes towards student government members were only involved to serve their own interests or the interests of only specific sub-populations of students. This sentiment may exist among student constituents, but these participants in this study did not experience those negative attitudes when they engaged with the student body.…”
Section: Student Voice For the Participants In This Study Student Vmentioning
confidence: 91%
“…The perception of student government decision-making that the student voters have is important. Findings in the literature showed that students who are represented by student government see those members in a negative light (Kennedy, Ginsburg, Harnois, & Spooner, 2015;Menon, 2003). Some students may view student government as serving the administration, only making decisions the institution tells them to make (Mackey, 2006;Miles, 2011).…”
Section: Faculty and Administrationmentioning
confidence: 99%
See 1 more Smart Citation